In vivo, micro‐morphological vascular changes induced by topical brimonidine studied by Dynamic optical coherence tomography. (25th February 2016) - Themstrup, L.; Ciardo, S.; Manfredi, M.; Ulrich, M.; Pellacani, G.; Welzel, J.; Jemec, G.B.E.
Abstract: Background: Brimonidine is a selective α2 adrenergic receptor agonist with potent vasoconstrictive activity topically used for treatment of facial flushing and erythema caused by rosacea. Direct evidence for the in vivo morphology changes in skin vessels induced by topical application of brimonidine is limited. Dynamic optical coherence tomography is a novel technology that combines conventional OCT with information on flow and thereby provides supplementary information about the microvasculature. Dynamic OCT is non‐invasive and creates high‐resolution in vivo images of skin to a depth of maximum 2 mm. Objective: The objective of this study was to examine and describe micro‐morphological skin vessel changes in normal skin exposed to brimonidine gel using Dynamic OCT. Materials and methods: A total of 35 healthy subjects from three European clinical dermatology centres were included in the study. A normal skin area on the cheek was marked and clinically photographed. Brimonidine gel 0.33% was applied on the area and chromaticity measurements; laser speckle measurements and Dynamic OCT images were acquired at baseline and 60 min after application. The images were subsequently described in detail and quantitatively analysed. Results: All the measurement tools (chromaticity, laser speckle, Dynamic OCT showed highly significant ( P < 0.001) quantitative differences in blood flow before and after the application of brimonidine. In 58% of the subjects the Dynamic OCT images showed notable changes in the morphology of the blood vessel network after application of brimonidine including a marked reduction in the abundance and the diameter of the blood vessels. Conclusion: The vascular constriction induced by topical brimonidine gel 0.33% was visualized in vivo by Dynamic OCT and confirmed by quantitative measurements and analyses. This study shows that Dynamic OCT can detect characteristic morphological changes in the vessels and may potentially aid the monitoring of treatment effects on skin vessels following topical or laser treatment.